The English wife - Willig, Lauren (St. Martin's Press, 2018)
Annabelle and Bayard Van Duyvil live a charmed life in New York: he's the scion of an old Knickerbocker family, she grew up in a Tudor house in England, they had a fairytale romance in London, they have three-year-old twins on whom they dote, and he's recreated her family home on the banks of the Hudson and named it Illyria. Yes, there are rumors that she's having an affair with the architect, but rumors are rumors and people will gossip. But then Bayard is found dead with a knife in his chest on the night of their Twelfth Night Ball, Annabelle goes missing, presumed drowned, and the papers go mad. Bay's sister, Janie, forms an unlikely alliance with a reporter to try to uncover the truth, convinced that Bay would never have killed his wife, that it must be a third party, but the more she learns about her brother and his wife, the more everything she thought she knew about them starts to unravel. Who were her brother and his wife, really? And why did her brother die with the name George on his lips?